ESSENSO: Meaning of Profit Oriented in Pharmacist’s Perspective - Bakhtiar, Yohan; Hamidah, Fitria Nur (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2022)
Profit in accounting is, all this time, still focused on anything material, but not on non-material aspects. This research aimed at reviewing the meaning of profit oriented in pharmacist’s perspective. This research used a qualitative approach with transcendental phenomenology as the analysis instrument. For ease of data analysis process, noema - noesis - intentional analysis - eidetic reductionmapping worksheet or paper was used. The research results show that profit for pharmacist can be of education, services, satisfaction, careness and economy. The synthesis of the five meanings is realized in the term ESSENSO (Education, Services, Satisfaction, Careness, and Economy) as the meaning concept of profit oriented in pharmacist’s perspective. Hopefully, with the benefits of ESSENSO, accounting profession can also apply it to its various scientific concentrations, including for educator accountant, public accountant, public sector accountant and management accountant.